Respiratory virus infections in symptomatic and asymptomatic children upon hospital admission: new insights - Zachary M. Most; Trish M. Perl; Michael Sebert (Cambridge University Press, 2024)
Abstract Objective: Describe and compare the prevalence of symptomatic and asymptomatic or recently resolved respiratory infections in hospitalized children. Design: Cross-sectional study. Setting: Three hospital primary-to-quaternary care pediatric healthcare system. Patients: People less than 22 years old who underwent admission screening for respiratory viruses using a multitarget polymerase chain reaction (PCR) panel from August 2020 through April 2022. Methods: The symptom status of each patient was recorded by the ordering provider. The prevalence of each virus was described comparing symptomatic and asymptomatic patients. Results for each virus were stratified by age group and trends were examined over time. Results: Of the 32,812 eligible PCR panels collected, 12,965 (39.5%), 18,651 (56.8%), and 1,196 (3.6%) were obtained from patients who were symptomatic, asymptomatic, or had missing or unknown symptom status, respectively. Symptomatic patients were much more likely to test positive for a respiratory virus (67.3% vs 27.0%). The most common viruses detected in asymptomatic patients were rhinovirus/enterovirus (18.0%), SARS-CoV-2 (3.6%), and parainfluenza viruses (2.3%). The odds ratio of testing positive when symptomatic was significantly greater than unity for all viruses but varied by virus and age group. The proportion of positive tests for each virus was dynamic and changed with intermittent epidemics, or viral "waves." Conclusions: More than one-quarter of children without respiratory symptoms admitted to a pediatric healthcare system had PCR-detectable respiratory viruses. Children with symptoms of a respiratory infection are nevertheless much more likely to have a respiratory virus detected by PCR.